Uzvārdi ar fizioģeogrāfiskas (paaugstināta reljefa) semantikas etimonu - Balodis, Pauls (Baltistica, 2012)
SURNAMES OF GEOGRAPHICAL(ELEVATED TERRAIN) ORIGINSummaryThe focus of the study is on Latvian personal names, which are coined on the the basis of Latvian apellative lexis. Personal names coined from the lexemes of the respective language, i.e., unborrowed anthroponyms, were chosen for comparison (in the Estonian, Finnish, Lithuanian, Polish, Russian and German language).There are many surnames of geographical origin (530 or 19.6% of all surnames of Latvian origin) in Latvian anthroponymic system and, according to their original meaning, they are very diverse: surnames, the etymon of which (a) indicates elevated or lowered terrain; (b) is connected to water courses and water bodies; (c) other surnames.There are around 180 compound surnames with the second component -kalns ʻ-hill’ and 13 with the second component -kalniņš ʻ-small hill’ in the reverse dictionary of V. Staltmane’s monograph, e.g. Rožkalns (45), Brīvkalns (40), Zaļkalns (37).In most cases these surnames have originated from homestead names or other toponyms, but calquing is also possible. There are several examples that show clear parallels between Latvian and Finno-Ugric languages, whereas the respective surname is not recorded in the modern German language system (e.g., Latv. Apškalns ‘hill of aspen trees’ – Est. Haavamägi (9), Haavamäe (11) – Finn. Haapamäki – German *Espenberg).There are several surnames of geographical origin recorded only in Latvian: Ābelskalns ‘apple-tree hill’ (3), Dzintarkalns ‘amber hill’ (1), etc.This semantic sub-group of geographical etymons is extensively represented in Finnish and Estonian surname system. There are many compound surnames, which do not have analogues in the Latvian language, among them – Etelämäki ‘south hill’, Tuiskuvaara ‘blizzard hill’.On the other hand, in German there are compound surnames with the second component -berg, which does not occur in Latvian, e.g. Brandberg ‘fire hill’, Schneeberg ‘snow hill’, etc.One can conclude that surnames of such semantic origin occur much more rarely in the Lithuanian, Polish and Russian languages, and there are almost no compound surnames including a lexeme with the meaning ‘hill’. There are clear parallels in the anthroponymic systems of Latvian and its closest Finno-Ugric neighbours (Estonian and Finnish). The influence of the German language is clearly seen in the structure of Latvian (as well as Estonian) surnames; however, it is not as extensive as it is usually suggested.
Keywords: Latvian; onomastics; surnames; elevated terrain; geographic semantics